2016
DOI: 10.1111/bcpt.12591
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Increases the Migration and Invasion of Triple‐Negative Breast Cancer Cells via Oestrogen‐related Receptor Gamma

Abstract: Triple-negative breast cancer (TNBC) is characterized by great metastasis and invasion capability. Our study revealed that nanomolar bisphenol A (BPA), one of the most ubiquitous endocrine disruptors, can increase wound closure and invasion of both MDA-MB-231 and BT-549 cells. BPA treatment can increase protein and mRNA expression of matrix metalloproteinase-2 (MMP-2) and MMP-9, while had no effect on the expression of vimentin (Vim) and fibronectin (FN) in TNBC cells. The expression of G-protein-coupled recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 42 publications
0
32
0
6
Order By: Relevance
“…We found that BPA-enhanced migration of EVT in a dose-dependent manner. BPA exposure also stimulates migration of several cancer cell lines in vitro [ 33 37 ]. However, these results are inconsistent with the finding that BPA inhibits the migratory and invasive abilities of HTR-8/SVneo cells at concentrations of 10 –11 M to 10 –7 M [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that BPA-enhanced migration of EVT in a dose-dependent manner. BPA exposure also stimulates migration of several cancer cell lines in vitro [ 33 37 ]. However, these results are inconsistent with the finding that BPA inhibits the migratory and invasive abilities of HTR-8/SVneo cells at concentrations of 10 –11 M to 10 –7 M [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9, an autocrine factor that localizes primarily to EVT cells at 6–8 weeks of human gestation, regulates trophoblast invasion and migration by degrading ECM [ 28 , 38 , 39 ]. BPA exposure induces expression of MMP s and cell migration in several cancer cell types [ 33 , 37 ]. We confirmed that MMP-9 and MMP-2 were involved in BPA-induced EVTs migration.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that BPA increases estrogen-related receptor γ (ERRγ) mRNA and protein levels in breast cancer cells [45]. An inverse agonist of ERRγ, GSK5182, increases iodine uptake and enhances membrane localization of NIS in anaplastic thyroid cancer cells [46].…”
Section: Discussionmentioning
confidence: 99%
“…FOXA1 repression is thought to be characteristic of EMT because it is an activator of the E-cadherin gene [62] . Exposure of the human breast cancer cell lines MDA-MB-231 and BT-549 led to increased invasiveness with an associated increased expression of MMP-2 and MMP-9 [63] .…”
Section: Bisphenol Amentioning
confidence: 99%